Integrasi Model TAM dan ECM dengan Faktor Eksternal UI untuk Menganalisis Niat Keberlanjutan Penggunaan Aplikasi Duolingo - Jessyca Adelia Saputri (Fakultas Ilmu Komputer, 2016)
The rapid growth of Mobile-Assisted Language Learning (MALL) has increased the adoption of language learning applications, with Duolingo emerging as one of the most widely used platforms. Despite its popularity, many users discontinue using the application after the initial adoption stage, highlighting the importance of understanding the factors influencing continuance intention. This study aims to evaluate the model fit of an integrated Technology Acceptance Model (TAM) and Expectation Confirmation Model (ECM) with User Interface (UI) as an external factor, identify the factors affecting continuance intention, provide recommendations for improving Duolingo, and examine the role of UI in strengthening the post-adoption mechanism. This research employed a quantitative approach using a survey of 150 undergraduate students in Indonesia who had used Duolingo for at least one month. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that the proposed model demonstrates a good fit (SRMR = 0.073). Continuance Intention is positively and significantly influenced by UI Structure (β = 0.323), Gamification (β = 0.276), UI Graphics (β = 0.248), and Perceived Usefulness (β = 0.132), while Application Design has a significant negative effect (β = −0.124). Furthermore, Confirmation positively and significantly affects Perceived Usefulness (β = 0.198) and Satisfaction (β = 0.769), whereas Price Value (β = 0.430) and Perceived Enjoyment (β = 0.256) positively and significantly influence Perceived Usefulness. Continuance Intention also has a positive and significant effect on Actual Use (β = 0.521). These findings confirm the importance of integrating TAM, ECM, and UI factors in explaining users' post-adoption behavior and provide practical recommendations for improving gamification, user experience, perceived usefulness, confirmation, and price value to encourage long-term use of Duolingo.
FINALISASI oleh Arif 2026 Agustus 11
Keywords: Duolingo; Technology Acceptance Model; Expectation Confirmation Model; User Interface; Continuance Intention